2016
DOI: 10.7324/japs.2016.60407
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous estimation of Esomeprazole and Tadalafil in pharmaceutical formulations using High Performance Liquid Chromatography

Abstract: An easily, specific, precise, and accurate reversed-phase HPLC method was developed and validated for simultaneous estimation of esomeprazole ( Nexium ® ) and tadalafil (Cialis ® ) in pharmaceutical formulation. The separation was achieved by using Hypersil BDS C18 column (250 mm × 4.6 mm; 5.0 μm) and acetonitrile: 0.05 M potassium dihydrogen phosphate buffer at pH 6 adjusted with phosphoric acid as a mobile phase at a flow rate of 1 mL/min. Detection was carried out at wavelength 285nm. The retention time of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It was found that our method is advantageous in various points. Regarding sensitivity, the developed approaches are more sensitive than the published methods [18–20, 22, 38, 39, 41, 46–49]. Furthermore, our method is the simplest and greenest approach for the analysis of the examined drugs in plasma samples.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…It was found that our method is advantageous in various points. Regarding sensitivity, the developed approaches are more sensitive than the published methods [18–20, 22, 38, 39, 41, 46–49]. Furthermore, our method is the simplest and greenest approach for the analysis of the examined drugs in plasma samples.…”
Section: Resultsmentioning
confidence: 98%
“…Its IUPAC name is (1,3-benzodioxol-5-yl)-2-methyl-2,3,6,7,12,12a-hexahydropyrazino[1 0 ,2 0 :1,6]-pyrido [3,4] indole-1,4-dione [6]. A literature survey displayed many analytical methods for TAD assay such as chromatographic methods [44][45][46], spectrophotometry [47][48][49][50], and spectrofluorimetry [42,51].…”
Section: Ava 4-((3-chloro-4-methoxybenzyl)amino)-2-(2-(hydroxymethyl)mentioning
confidence: 99%